PromA Plasmids Are Instrumental in the Dissemination of Linuron Catabolic Genes Between Different Genera - Werner, Johannes; Nour, Eman; Bunk, Boyke; Spröer, Cathrin; Smalla, Kornelia; Springael, Dirk; Öztürk, Başak (Frontiers in Microbiology, 2020)
PromA plasmids are broad host range plasmids, which are often cryptic and hence have an uncertain ecological role. We present three novel PromA γ plasmids which carry genes associated with degradation of the phenylurea herbicide linuron, two (pPBL-H3-2 and pBPS33-2) of which originate from unrelated Hydrogenophaga hosts isolated from different environments, and one (pEN1) which was exogenously captured from an on-farm biopurification system. Hydrogenophaga sp. plasmid pBPS33-2 carries all three necessary gene clusters (hylA, dca, ccd) determining the three main steps for conversion of linuron to Krebs cycle intermediates, while pEN1 only determines the initial linuron hydrolysis step. Hydrogenophaga sp. plasmid pPBL-H3-2 exists as two variants, both containing ccd but with the hylA and dca gene modules interchanged between each other at exactly the same location. Linuron catabolic gene clusters that determine the same step were identical on all plasmids, encompassed in differently arranged constellations and characterized by the presence of multiple IS1071 elements. In all plasmids except pEN1, the insertion spot of the catabolic genes in the PromA γ plasmids was the same. Highly similar PromA plasmids carrying the linuron degrading gene cargo at the same insertion spot were previously identified in linuron degrading Variovorax sp. Interestingly in both Hydrogenophaga populations not every PromA plasmid copy carries catabolic genes. The results indicate that PromA plasmids are important vehicles of linuron catabolic gene dissemination, rather than being cryptic and only important for the mobilization of other plasmids.